SUITABILITY OF THE ESTABLISHMENT OF THE PROTECTED NATURAL AREA OF THE TROPICAL PACIFIC SEA - Hopkins Alfaro, José Diego (2019)
In this essay we will analyze the suitability of the establishment of the Marine Protected Area (MPA) of the Tropical Pacific Sea, which would be located off the coast of Piura and Tumbes. Based on an analysis of the literature regarding the design and implementation of MPAs, we will point out some aspects that should be taken into account by administrators and decision makers in all the stages related to the process of assigning the MPA figure to a specific geographical area. Also, we will review the official documentation developed in the proposal process by various state agencies. The objective of this essay is to provide insights into the correct preparation of a proposal that changes the legal system on which the geographical area chosen to be protected rests.